Executive Social Network and Enterprise Innovation - Zhang, Juan (Journal of Accounting, Business and Finance Research, 2019)
This paper tests the impact of executive social network on enterprise innovation, and analyzes the impact of executive social network on the innovation of target enterprises and connected enterprises. Through empirical research, we find that the executive social network significantly promotes enterprise innovation, indicating that the available resources embedded in the executive social network have played their roles. In addition, based on the organizational learning theory and Mosaic theory, this paper finds that the innovation level of enterprises with executive social network has been significantly improved. Furthermore, when the sample is divided into target companies and connected companies, the empirical results show that the innovation level of connected companies is significantly improved. Through communication and successful experience exchange, the innovation level of connected enterprises is improved.